Pelatihan dan Pendampingan Model Pembelajaran Inovatif dan Kreatif Bagi Calon Guru Fisika - Herayanti, Lovy; Gummah, Syifa’ul; Sukroyanti, Baiq Azmi; Ahzan, Sukainil; Azmi, Irham; Hikmah, Nurul; Al-Haris, Umar (Indonesian Journal of Education and Community Services, 2023)
This community service program aims to enhance the pedagogical and professional competence of pre-service physics teachers at FSTT UNDIKMA through training and mentoring in the development of innovative instructional materials. The rationale for this program is underscored by the necessity for instructional adaptation in the digital era, requiring prospective teachers to integrate physics content, pedagogy, and technology (TPACK). The implementation method employed a participatory approach comprising four stages: preparation, workshops, simulation (teaching practice), and continuous mentoring. The results indicate a significant improvement in participants' understanding of various instructional models, such as Project-Based Learning (PjBL) and Inquiry, as well as their technical skills in developing digital and simulation-based media. Ultimately, this program successfully shifted the students' teaching paradigm toward a more student-centered and technology-adaptive approach.